Estudio de la producción de ácido linoleico conjugado por cepas de lactobacillus y enterococcus de distintos orígenes - Conte-junior, Carlos A.; Soncin, Silvia (Revista Complutense de Ciencias Veterinarias, 2007)
Conjugated linoleic acid (CLA) is a mixture of isomers of linoleic acid with conjugated double bonds. Several studies related the isoforms of CLA with beneficial effects such as anticarcenogenic activity, antiatherogenic activity, the ability to reduce body fat or to improve immune system function. Ruminal bacteria are the main responsible for CLA production. However other bacteria are also able to produce CLA from linoleic acid, such as Bifidobacterium, Enterococcus and Lactobacillus sp. The aim of this research was to evaluate the ability of several strains of Lactobacillus and Enterococcus isolated from different sources to produce CLA in order to use them for the production of functional foods. The results showed that the cis-9,trans-11 CLA isomer was the dominant one in all the strains studied. Lactobacillus gasseri LM21 was the main producer when incubated in anaerobiosis for 48 hours.